2021
DOI: 10.3390/curroncol28040269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of the COVID-19 Pandemic on New Cancer Diagnoses and Oncology Care in Manitoba

Abstract: Individuals with cancer are vulnerable to infection with SARS-CoV-2, the virus causing COVID-19. Physical distancing, the reallocation of health care resources, and the implementation of procedures to reduce the spread of COVID-19 may also have serious consequences for people with cancer. We evaluated the impact of COVID-19 on new cancer diagnoses and oncology care in Manitoba, Canada using an interrupted time series design and data from the Manitoba Cancer Registry and CancerCare Manitoba’s (CCMB) electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 20 publications
3
25
0
1
Order By: Relevance
“… 3 Reductions in cancer diagnoses similar to those in Ontario have been reported elsewhere. 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 In line with our findings, a study from Italy reported a 17% reduction in radiotherapy. 18 Another study from Spain reported reductions of 37% in new oncology referrals and 38% in new treatments, 19 substantially greater reductions than those observed in Ontario.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“… 3 Reductions in cancer diagnoses similar to those in Ontario have been reported elsewhere. 4 , 5 , 7 , 12 , 13 , 14 , 15 , 16 , 17 In line with our findings, a study from Italy reported a 17% reduction in radiotherapy. 18 Another study from Spain reported reductions of 37% in new oncology referrals and 38% in new treatments, 19 substantially greater reductions than those observed in Ontario.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to our findings, which demonstrated that systemic treatment visits were largely unchanged, a national study from Scotland reported a 29% reduction in systemic therapy visits in March 2020. 20 However, a study from the Canadian province of Manitoba reported little change in parenteral chemotherapy visits, 17 where similar interim measures were used (eg, shorter regimens). Such differences are expected, given the variability in timing of pandemic waves, policy directives, and clinical guidance.…”
Section: Discussionmentioning
confidence: 99%
“…11 Analysis of the Manitoba Cancer Registry showed a 23% decrease in new cancer diagnoses in April 2020, accompanied by a 21% decrease in the volume of pathology reports and a 43% drop in surgical resections. 12 Quebec data revealed a 5% decrease in pathology results positive for malignancy in 2020 to 2021 compared with the previous year. 4 Canada-wide, the number of cancer surgeries decreased by about 20% in 2020 compared with 2019.…”
Section: Impacts On Cancer Screening and Diagnosismentioning
confidence: 89%
“…There are multiple reports of delay in diagnosis and treatment of patients with chronic diseases, including cancer [ 21 , 22 ]. The increased mortality and morbidity from delay in diagnosis and treatment may only emerge at a later stage [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%